Application of Roy’s Adaptation Model and Swanson’s Caring Theory in Nursing Care for Post–Hydatidiform Mole Patients: A Case-Based Study - Atun Raudotul Marifah; Setyowati; Yati Afiyantiyati (Journal of Applied Holistic Nursing Science, 2026)
ABSTRACT Background: Nurses play a key role in improving women’s reproductive health through theory-based care. Gestational trophoblastic disease, including hydatidiform mole, is a high-risk condition with potential physical and psychological impacts. This study aimed to describe the application of Roy’s Adaptation Model and Swanson’s Caring Theory in nursing care for post–hydatidiform mole patients after curettage Methods: A descriptive case-based approach was conducted in a referral hospital. Data were collected through comprehensive nursing assessments covering physiological, self-concept, role function, and interdependence domains, along with focal, contextual, and residual stimuli. Nursing diagnoses, interventions, and evaluations were developed using Roy’s Adaptation Model and integrated with Swanson’s five caring processes. Results: Theory-guided care improved bleeding and infection risk management, reduced anxiety, and enhanced patient understanding and adherence to follow-up care, including β-hCG monitoring. Adaptive responses were particularly evident in psychological adjustment and coping. Conclusion: The integration of Roy’s Adaptation Model and Swanson’s Caring Theory enhances adaptive capacity and supports recovery in post–hydatidiform mole patients, highlighting the importance of strengthening nurses’ theoretical competencies.